Worked example or scripting? Fostering students' online argumentative peer feedback, essay writing and learning. Issue 2 (17th February 2023) - Latifi, Saeed; Noroozi, Omid; Talaee, Ebrahim
ABSTRACT: This study compared the effects of worked example and scripting on students' argumentative peer feedback, essay and learning qualities. Participants were 80 BSc students who were randomly divided over 40 dyads and assigned to two experimental conditions (worked example and scripting). An online peer feedback environment named EduTech was designed and students were tasked with writing an argumentative essay, engaging in peer feedback, and revising their essay. The results indicate that students in the scripting condition benefited more than students in the worked example condition regarding peer feedback quality. Furthermore, the scores of students in both conditions improved from pre-test to post-test in terms of argumentative essay writing and learning. This difference was significant, however, between the two conditions only with regard to argumentative essay writing favoring the scripting condition. We explain how each of these approaches can be used to improve students' argumentative peer feedback and essay writing and learning.